Structural Balance Targeting and Output Gap Uncertainty - Tereanu, Eugen (IMF Working Papers; Working Paper ;, 2014)
Potential output estimation plays a crucial role in conducting fiscal policy based on structural balances. Difficulties in estimating potential output could lead to an erroneous policy stance with a consequent impact on growth. This paper analyzes historical data on revisions of actual and potential growth in the European Union and the implication of these revisions for the measurement of fiscal effort using the cyclically-adjusted primary balance (CAPB). It finds that revisions in output gap estimates were large, at almost 1 1\2 percent of potential GDP on average. Revisions in potential GDP also contributed significantly to revisions in the estimated CAPB, especially during the crisis years. Given these findings and historical correlations, it proposes an indicative rule of thumb for reducing errors in the measurement of fiscal effort by factoring in that about 30 percent of revisions in actual growth capture changes in potential growth. In other words, the standard advice of 'letting automatic stabilizers operate fully' in response to a positive/negative growth shocks likely implies a strengthening/weakening of the structural position.